Perceptions on wearable sensor-based interventions for monitoring of opioid therapy: A qualitative study - Chapman, Brittany P.; Lucey, Evan; Boyer, Edward W.; Babu, Kavita M.; Smelson, David; Carreiro, Stephanie (Frontiers in Digital Health, 2022)
Prescription opioid use is a risk factor for the development of opioid use disorder. Digital solutions, including wearable sensors, represent a promising opportunity for health monitoring and risk stratification in this treatment space. However, data on their usability and acceptability in individuals taking prescription opioids is limited. To address this gap, factors that impact usability and acceptability of wearable sensor-based opioid detection were studied in participants enrolled in a wearable sensor-based opioid monitoring research study. At the conclusion of the monitoring period, participants were invited to take part in semi-structured interviews developed based on the technology acceptance model. Thematic analysis was conducted first using deductive, then inductive coding strategies. Forty-four participants completed the interview; approximately half were female. Major emergent themes include sensor usability, change in behavior and thought process related to sensor use, perceived usefulness in sensor-based monitoring, and willingness to have opioid use patterns monitored. Overall acceptance for sensor-based monitoring was high. Aesthetics, simplicity, and seamless functioning were all reported as key to usability. Perceived behavior changes related to monitoring were infrequent while perceived usefulness in monitoring was frequently projected onto others, requiring careful consideration regarding intervention development and targeting. Specifically, care must be taken to avoid stigma associated with opioid use and misuse. The design of sensor systems targeted for opioid use must also consider the physical, social, and cognitive alterations inherent in the respective disease processes compared to routine daily life.